Reproductive Disorders in Beef Cattle in Kerek Subdistrict, Tuban Regency, Indonesia - Prastiya, Ragil Angga; Ma'ruf, Mohammad Arief; Sari, Sera Yunita (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Tuban regency is one of the second largest beef cattle producers in East Java after Sumenep Regency with a total 344.203 beef cattle population. Based on the cases of reproductive disorders of beef cattle data in Tuban Regency from 2018 until 2019 reported the incidence of reproductive disorders was as many as 8.501. Treatment of reproductive disorders in Kerek Subdistrict, Tuban found 797 cases of reproductive disorders from 9.150 total population. The purpose of this study is to identify how several factors, namely feed, age, and cage environment contributes to cases of reproductive disorders in beef cattle in Kerek Subdistrict, Tuban Regency in 2018-2019. The samples used in this study were 131 cows with reproductive disorders. The method used in this study was the survey method and obtained primary and secondary data.  Primary data were obtained from field surveys of farmers, Secondary data was obtained from the examination of reproductive disorders in beef cattle by the Department of Fisheries and Livestock. The data obtained were then tabulated and analyzed with a chi-square test. The results showed that feed variables, age, and cage environment can affect the occurrence of reproductive disorders in beef cattle in The District Kerek, Tuban.Keywords: Reproductive health, Reproductive disorders, Beef Cattle, Livestock